PATH-34. SOLITARY FIBROUS TUMOR: NATURAL HISTORY AND PROGNOSIS IN ACCORDANCE WITH THE WHO 2021 CLASSIFICATION OF CNS TUMORS. (14th November 2022) - Eschbacher, Kathryn; Jenkins, Sarah; Fritchie, Karen; Moskalev, Evgeny; Caron, Alissa; Link, Michael; Brown, Paul; Guajardo, Andrew; Brat, Daniel; Wu, Ashely; Santagata, Sandro; Louis, David; et al.
Abstract: Meningeal solitary fibrous tumor (SFT) is a rare tumor with high propensity to recur and metastasize, even late in the course of disease. The WHO 2021 classification of CNS tumors divides SFT in 3 grades, based on mitotic index and necrosis. We re-examined our cohort of 126 patients (57 F, 69 M; mean age 53.0 years) with SFT, confirmed by STAT6 nuclear positivity and/or NAB2::STAT6 fusion, with extended follow-up (median 7.6 years; range 4 days-26.6 years). Tumors included 76 grade 1, 36 grade 2 and 14 grade 3 according to 2021 WHO criteria, evaluated at primary resection (n=90), recurrence (n=35), or metastasis (n=1). Fifty-six patients had one or more post-surgical events, the earliest event being local recurrence (n=41) or metastasis (n=15). Forty patients died (29 of disease; 9 of other causes; 2 unknown). Overall survival (OS), and progression-free survival (PFS, recurrence and/or metastasis) from time of primary resection (n=90) were not significantly associated with grade; however, risk of metastasis differed significantly (5-year estimates: 4.1%, 15.3%, and 37.8% for grades 1, 2, and 3 SFT, respectively; p=0.005). NAB2::STAT6 fusion status was known in 101 cases (51 = ex5-7-ex16-17, 26 = ex4_ex2-3; 12 = ex2-3_exANY/other and 12 =no fusion). Disease specific 5-year survival in primary tumors with molecular data (n = 75) was 80.0% in patients whose tumors harbored ex5-7_ex16-17 compared to 93.3% in all others combined (p=0.014). Targeted TERT promoter mutation testing was performed in 98 patients, revealing patients with tumors lacking TERT promoter mutation (n = 88) were younger at time of surgery than those harboring a mutation (n=10; p = 0.022), and none with a mutation harboring concurrent ex5-7_ex16-17 fusion (p = 0.0009). In summary, WHO 2021 grade is associated with risk of metastasis. Patients whose tumors harbor ex5-7_ex16-17 fusion have a higher risk of dying from the disease.